Feel happy now! - Neill, Michael (Australia : Hay house India, 2007)
Reveals the 'how' of happiness - simple, effective ways to beat stress, overcome anxiety, move beyond depression and reap the benefits of feeling happy, in spite of it all. This book helps you find the Happy Formula - three simple steps that can enable you to feel good, feel better and even feel happy in any situation.
Keywords: Happiness; Self-actualization (Psychology).